Evaluation of a teaching hospital necropsy service. - Fowler, E F (1977)
The information returned to the hospital clinician after a necropsy was investigated in a series of 1000 patients. It was found that specific clinical queries were answered in 83% of cases, that the necropsy corrected the major clinical diagnosis in 36% of cases, and that 29% of cases were used for undergraduate or postgraduate teaching. The results demonstrate the continuing value of the necropsy as an investigative and educative procedure.